“The Third Image”: Ekphrasis and Memory in Charles Simic’s Dime-Store Alchemy: The Art of Joseph Cornell - Ambroży, Paulina (Hungarian Journal of English and American Studies, 2020)
In his collection of prose-poems, Dime-Store Alchemy: The Art of Joseph Cornell, Charles Simic evokes the American artist’s aesthetic practice as a form of meditation on the heterosemiotic nature of the artistic imagination. Cornell’s art, often described as “visual poetry,” becomes for Simic a pretext for exploring the multimodal and interconnected spaces of the verbal and the visual. Simic describes his creative rereading of Cornell’s work as “the third image” in which art historical discourse and ekphrasis are reinvented and transformed into a new poetic rhythm. The poet’s engagement with Cornell is also of an intensely personal character: the encounter with the artist’s work enables Simic to revisit his own past, that is, that of a lonely Manhattan flaneur whose imagination is haunted by traumatic childhood memories from war-torn Serbia. With the aid of Jacques Lacan’s concepts of the gaze and the screen, the article examines the ways in which Simic’s texts and visual intertexts probe generic boundaries and discursive identifications, showcasing the significance, function, and creative value of cross-influence between heterogeneous discourses and media. As shown, Simic’s concept of “the third image,” which finds its inspiration in the tension between containment and freedom in Cornell’s shadow boxes, offers readers a rich and personal insight into the complex interplay between discursivity, visuality, figurality, as well as personal and collective memory. (PA)